Paper-based Verification Design of Trade Business License in Indonesia - Pizaini Pizaini; Sugi Guritman; Heru Sukoco (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The trade business license certificate (SIUP) is a paper-based license to conduct trade businesses in Indonesia issued by the government. Until today, there is no mechanism for verifying the validity of document unless to verify it manually. The current paper presents a design that allows paper-based verification of the printed trade business license. It aims to provide the verification mechanism and ensure the document validity. Our design implemented digital signature with QR Code image that placed into the document and the digital certificate issued by a certification authority (CA). The proposed scheme generated 442Bytes of data and version 14 of QR Code to scan easily by a reader device. The experimental result indicates that our scheme is easy and feasible to implement in Indonesia with guaranteed the document integrity, authentication, and nonrepudiation.